Politeness in Indonesian as a Reflection of Students' Religious Character: A Phenomenological Study in Higher Education - Mahas, Nurul Hudayanti (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Linguistic politeness is a fundamental manifestation of a person's character, reflected in everyday communicative interactions. Linguistic politeness plays a vital role in shaping students' social and spiritual identities. Understanding how linguistic politeness functions as an indicator of students' religious character in the digital era, which is full of challenges to traditional values, is urgently needed. Therefore, this study aims to examine the phenomenon of Indonesian language politeness as a reflection of students' religious character in higher education. Using a qualitative phenomenological approach, this study involved 40 students at As'adiyah Sengkang Islamic University from various faculties. Data collection was conducted through in-depth interviews, participant observation, and analysis of written communication documents. The findings indicate that students' linguistic politeness reflects the internalization of Islamic values using politeness formulas, the selection of appropriate diction, and communication patterns that respect social hierarchy. Factors shaping politeness include the religious environment of the campus, lecturer guidance, and the still-strong tradition of Islamic boarding schools. This study contributes to the development of a pragmatic theory of politeness in the context of Islamic higher education and provides practical recommendations for student character development.